Zarządzanie placówką wychowania przedszkolnego uwikłaną w konflikty = Managing a preschool facility embroiled in conflicts - Morgała, Monika (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The study presented in this paper aimed to answer three questions: how do conflicts occurring within teaching staff affect the evaluation of the quality of pre-school facility management; what conflict management styles are displayed by directors; and how are these facilities managed. The sample included 305 female teachers and 37 female directors employed in public and non-public kindergartens and other pre-school educational establishments.
Keywords: teaching staff; conflict; pre-school facilities; management in education; zespół nauczycielski; konflikt; placówka wychowania przedszkolnego; zarządzanie w edukacji